Peran Majelis Taklim Al-Hidayah dalam Meningkatkan Pemahaman Keagamaan Anggotanya - Muzakkiyah, Nurul (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2024)
Seeking knowledge is not only done by children but also parents in the midst of their daily activities. So parents are looking for other alternatives to gain knowledge, especially religious knowledge, including through the taklim assembly, in this case the Al-Hidayah taklim assembly. This community service activity begins with observing and then continues with implementing community service programs. Among them are faith formation, sakinah family education, empowerment of the needy, improving the family economy, a place to learn religious knowledge, and harmony between religious communities.